Comparison between patients who have undergone cancer surgery based on MST value: a retrospective study. - ADRIAN, Wina; AS'AD, Suryani; SYAUKI, A Yasmin; .; TASLIM, Nurpudji A.; ASHARI, Nur (Nutrición Clínica y Dietética Hospitalaria, 2025)
Abstract Introduction: Malnutrition is a prevalent concern in oncologic surgery patients, often exacerbated by the effects of cancer and its treatments. Malnutrition is associated with poor clinical outcomes, including higher mortality rates, longer hospital stays, and increased complications. The Malnutrition Screening Tool (MST) is a valuable method for identifying malnutrition risk at hospital admission. This study aims to assess the prevalence of malnutrition using the MST and evaluate its prognostic value in relation to clinical outcomes, such as length of stay (LOS), inflammatory markers, and mortality in oncologic surgery patients. Methods: A retrospective cohort study was conducted at Dr. Wahidin Sudirohusodo Hospital in Makassar, Indonesia, from January 2022 to January 2024. Nutritional status was assessed using the MST, and key clinical outcomes—LOS, inflammatory markers (Neutrophil-to-Lymphocyte Ratio [NLR]), serum albumin, total lymphocyte count (TLC), and Prognostic Nutritional Index (PNI)—were analyzed. Statistical comparisons were performed using chi-square tests and t-tests, with statistical significance set at p < 0.05. Results: Among the 284 patients, 33.8% were classified as malnourished (MST ≥2). Patients with higher MST scores had significantly worse clinical outcomes, including higher mortality (33.3% vs. 12.3% for MST <2, p < 0.001). Malnourished patients exhibited poorer inflammatory and nutritional markers, with higher NLR (6.13 vs. 4.68, p = 0.05), lower albumin (3.0 g/dL vs. 3.3 g/dL, p = 0.004), and lower PNI (36.4 vs. 41.8, p < 0.001). No significant difference was found in LOS between the two groups (median 10 days vs. 9 days, p = 0.732). Conclusion: Malnutrition, as identified by the MST, is strongly associated with increased mortality and worsened inflammatory and nutritional markers in oncologic surgery patients. These findings underscore the need for routine nutritional screening and timely interventions to improve clinical outcomes in this high-risk population.